Rapid weight reduction in judo: dietary practices and short-term health effects - Staskiewicz-Bartecka, W.; Ziomek, P.; Dobkowska-Szefer, D.; Malchrowicz-Mosko, E.; Tomaszewski, P. (Nutrients, 2025)
Background: Rapid weight loss (RWL) is a widespread practice among judo athletes seeking to compete in lower weight categories. Restrictive nutritional and behavioral strategies used to achieve short-term reductions in body mass may impair physiological and psychological functioning. This study aimed to assess dietary behaviors, weight-cutting methods, and short-term physical and psychological effects of RWL among competitive judo athletes. Methods: A cross-sectional study was conducted between August and December 2024 among 70 judo athletes (17 women, 53 men) competing at national and international levels. Data were collected using an author-designed questionnaire addressing anthropometric variables, training history, RWL strategies, dietary restrictions, hydration manipulation, and post-weigh-in eating behaviors. Physical and psychological symptoms were assessed using frequency-based self-report measures. Results: Most athletes (95.7%) reported engaging in RWL, typically beginning between ages 13 and 16 years (65.7%). Athletes reduced an average of 3.64 ± 1.74 kg (2-5% of body mass). Common strategies included decreasing meal frequency (74.29%), increasing training load (72.86%), restricting fluids (68.57%), and using saunas (62.86%). Reported physical symptoms included weakness (71.43%), headaches (51.43%), and dizziness (45.71%), while psychological symptoms included irritability (57.14%), reduced motivation (40%), and tension (38.57%). Post-weigh-in binge eating occurred in 65.71% of athletes and was significantly associated with higher RWL magnitude (p < 0.05). Discomfort during competition related to overeating (55.71%) or insufficient intake (41.43%) was also frequent. Conclusions: RWL is highly prevalent among judo athletes and often begins early in training history. The strategies used are associated with adverse physical and psychological symptoms and maladaptive compensatory behaviors. These findings highlight the need for evidence-based nutritional education and individualized weight-management approaches to support athlete health and performance.